Barrett's oesophagus: A qualitative study of patient burden, care delivery experience and follow‐up needs. (14th November 2018) - Britton, James; Hamdy, Shaheen; McLaughlin, John; Horne, Maria; Ang, Yeng
Abstract: Background: Barrett's oesophagus (BO), a precursor to oesophageal adenocarcinoma, requires long‐term endoscopic surveillance. The rising incidence of this chronic disease has implications for service provision and patient burden. Few studies have explored BO patients' personal burden, care delivery experience and participation in health‐care delivery decisions. Objective: To identify and explore factors impacting BO patients' health‐related quality of life, follow‐up needs and views on new models of follow‐up care. Design: An exploratory qualitative approach was adopted using semi‐structured, in‐depth, one‐to‐one interviews, audio‐recorded and transcribed verbatim. Patients undergoing BO surveillance, at a single NHS hospital, were recruited using purposive sampling with the aim of achieving maximum variation. Data were analysed using framework analysis approach, supported by NVivo Pro 11. Results: Data saturation occurred after 20 participant interviews. Ten subthemes and three main themes emerged from the analysis: (a) burden of disease—symptom control, worry of oesophageal cancer and surveillance endoscopy; (b) follow‐up experiences—follow‐up care, at this NHS hospital, was found to be inconsistent and often inadequate to meet patients' needs, in particular a lack of disease‐specific information; and (c) follow‐up needs—participants sought enhanced communication, organization and structure of care. They highly valued face‐to‐face interaction with a specialist, and the concept of direct secondary care access in‐between endoscopies was reassuring to participants. Conclusions: This qualitative research provides an in‐depth account of the patients' perspective of BO, the effectiveness of follow‐up care and patient opinion on new follow‐up systems.